GENERAL PRINCIPLES OF EU (CRIMINAL) LAW: LEGALITY, EQUALITY, NON-DISCRIMINATION, SPECIALTY AND NE BIS IN IDEM IN THE FIELD OF THE EUROPEAN ARREST WARRANT - NOREL NEAGU (Challenges of the Knowledge Society)
This article deals with the case law of the Court of Justice of the European Union in the field of the European arrest warrant, critically analysing the principles invoked in several decisions validating the European legislation in the field: legality, equality and non-discrimination, specialty, ne bis in idem. The author concludes that an area of freedom, security and justice could be built on these principles, but further harmonisation of legislation needs to be realised to avoid a ”journey to the unknown” for European citizens in respect to legislation of other member states of the EU.